‘Memanusiakan Manusia’ dalam Lingkungan yang Tangguh: Mengapa ‘Jauh Panggang dari Api’? - Yunita T Winarto (Antropologi Indonesia, 2013)
It is a reality that our environment has become degraded due to various human activities without any concerns for the long-term sustainable implication on both nature and the people who have for generations developed social-cultural institutions to protect their environment in a sustainable manner. The problems have been more severe due to the alienation of local people in their own habitat and the replacement of their roles by those who have power and authority in introducing various kinds of development programmes. There have been no linkages between the physical and natural processes as the consequences of those programmes with people’s empirical knowledge. It is now high time to “humanize people” again in their own environment. An interdisciplinary approach is indeed necessary. Anthropology can play a significant role in providing the “knot” in the network of science-technology-policy on the one hand, and people’s lives on the other hand. Trans-disciplinary research and collaboration with local people have to be developed further. Anthropologists can be the “cultural translators” for various parties who have different objectives, knowledge, perspectives, and strategies in resource management. This inauguration paper addresses this issue by exemplifying the problems faced by farmers in Indonesia who have been alienated in their own lands since the onset of the Green Revolution in food crop production and how an anthropologist can contribute to the return of farmers’ dignity and creativity.Key-words: farmers’ alienation, humanizing people, inter- and trans-disciplinary collaboration, cultural mediator and translator, Science Field Shop